Developing a PBL-Based Physics Website to Enhance Students’ Critical Thinking and Learning Motivation - Siti Nurhalisa; Romi Aprianto; Syarif Fitriyanto (Indonesian Publication Center, 2026)
The low physics achievement at MAN 2 Sumbawa (85% of students below the mastery criterion in Heat–Temperature) highlights the need for pedagogical innovations aligned with 21st-century skills. This study aims to validate, assess the practicality, and test the effectiveness of a Problem-Based Learning (PBL) physics website developed via Canva. The ADDIE model was applied to 19 eleventh-grade students over three meetings. Validity, assessed by two subject and two media experts using a 4-point Likert rubric, yielded Aiken’s V of 0.81–0.93 with average feasibility of 82.5% (content) and 86.46% (media), classified as “very valid.” Practicality, measured through teacher and student questionnaires (scale 1–5), scored 81.88% (teachers) and 87.90% (students), indicating “very practical.” Effectiveness analysis using N-Gain and paired t-test (? = 0.05) showed learning motivation rising from 44% to 92% (N-Gain = 0.86; high) and critical thinking from 34% to 69% (N-Gain = 0.53; medium), both p < 0.001. These results confirm Canva–PBL integration as an affordable, replicable solution to enhance physics students’ motivation and critical thinking in resource-limited schools.